EFEKTIVITAS PENGGUNAAN TEKNOLOGI SMARTBOARD TERHADAP KEMAMPUAN LITERASI SAINS PADA MATERI EKOSISTEM PEMBELAJARAN IPAS KELAS V UPTD SD NEGERI 125543 - Theresia Elisabet Siburian; Aprido Bernando Simamora; Asister Fernando Siagian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science literacy is an essential competency in 21st-century learning as it supports critical thinking and evidence-based decision-making. This study aims to analyze the effectiveness of SMARTBOARD technology in improving students’ science literacy skills on ecosystem material in Grade V IPAS learning at UPTD SD Negeri 125543. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest design. The subjects consisted of 25 fifth-grade students. The research instruments included essay tests and observation sheets to assess learning implementation. Data analysis was conducted using Aiken’s V index for instrument validity and the N-Gain test to measure learning improvement. The results showed that the average pretest score of 53.8 increased to 85.4 in the posttest, with an N-Gain value of 0.64 categorized as moderate. Additionally, the observation results indicated a 96.87% implementation rate, classified as very good. These findings demonstrate that the use of SMARTBOARD is effective in enhancing students’ science literacy through interactive and visual-based learning. Therefore, SMARTBOARD can serve as an innovative instructional medium to support the improvement of science literacy in elementary education.